2015
DOI: 10.1371/journal.pone.0143069
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ghrelin Gene Polymorphisms and Serum Ghrelin Levels with the Risk of Hepatitis B Virus-Related Liver Diseases in a Chinese Population

Abstract: BackgroundThe functions of ghrelin (GHRL) include anti-inflammatory effects, reduction of the fibrogenic response, protection of liver tissue, and regulation of cell proliferation. Genetic variations in the GHRL gene may play an important role in the development of chronic hepatitis B (CHB), liver cirrhosis (LC) and hepatocellular carcinoma (HCC). Therefore, we investigated whether GHRL gene polymorphisms and its serum levels are associated with hepatitis B virus (HBV)-related diseases risk in a Chinese popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…The etiology of the disease has been widely studied, and previous research has demonstrated that many environmental and lifestyle factors, such as hepatitis B/C virus infection, aflatoxins, long-term alcohol consumption and liver cirrhosis (Nguyen et al, 2009;Liu et al, 2012;Niu et al, 2016). Previous studies have demonstrated that many genetic variations contribute to the risk of developing hepatocellular carcinoma, including C-reactive protein, Holliday junction recognition protein (HJURP), epidermal growth factor 61A/G, and Ghrelin and FasL genes (Lao et al, 2015;Shen et al, 2015b;Zhang et al, 2015a;Huang et al, 2016;Khalifa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of the disease has been widely studied, and previous research has demonstrated that many environmental and lifestyle factors, such as hepatitis B/C virus infection, aflatoxins, long-term alcohol consumption and liver cirrhosis (Nguyen et al, 2009;Liu et al, 2012;Niu et al, 2016). Previous studies have demonstrated that many genetic variations contribute to the risk of developing hepatocellular carcinoma, including C-reactive protein, Holliday junction recognition protein (HJURP), epidermal growth factor 61A/G, and Ghrelin and FasL genes (Lao et al, 2015;Shen et al, 2015b;Zhang et al, 2015a;Huang et al, 2016;Khalifa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been suggested that other GHRL gene polymorphisms are significantly associated with circulating levels of glucose [49], insulin [46], metabolic syndrome [50], hypertension [51], and hepatocellular carcinoma [52]. And finally, serum levels of ghrelin decrease in the patients with either liver advanced fibrosis or liver cirrhosis and GHRL gene variants influence the progression of liver fibrosis and liver cirrhosis [53,54]. The other possible hypothesis linking the rs696217 polymorphism with NAFLD risk is through linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs were reported to be involved in HBV-related liver diseases. Zhang X et al observed that, in healthy controls, the ghrelin rs26311 GC+CC genotype increased the risk of LC in contrast to the GG genotype ( P = 0.034), especially in males ( P = 0.042) 25 . Healthy individuals carrying toll-like receptor 3 (TLR3) rs3775290 TT genotype had a decreased risk for CHB, HBV-related LC and HCC 26 .…”
Section: Discussionmentioning
confidence: 99%